Spatial frames of reference for literature using geospatial technologies - Priestnall, Gary
This book chapter focuses on the use of three-dimensional representations of landscape, where digital terrain data is used as a backdrop to place cultural heritage information including passages from works of literature, diaries, and sketches, into a broader landscape context. Three case studies, which offer examples of different presentation techniques, one based on a computer monitor, one on a physical landscape model, and one on a mobile device, are described. The studies engage with the same geographic area, upland Cumbria in North West England, where surface relief is a dominant feature of the landscape. Each case study, however, uses different technologies appropriate to the contexts of display and a set of stated aims. The chapter summarises the affordances of each technique, presents observations from their use, and discusses some of the opportunities and design challenges that apply when utilising geospatial technology and digital landscape models for communicating spatial context.